Left ventricular assist devices and gastrointestinal evaluation: Results of a consecutive case series. (1st February 2017) - Alotaibi, Sultan; Erbel, Raimund; Neumann, Till
Abstract: Aims: To evaluate the benefit of preoperative gastrointestinal endoscopic evaluation in patients undergoing continuous flow left ventricular assist devices (CF-LVADs) implantation. Methods and results: A retrospective review of all fifty-three patients undergoing CF-LVADs at West-German Heart and Vascular Center, University of Duisburg-Essen was performed. A routine preoperative esophagogastroduodenoscopy was performed in seven patients to assess gastrointestinal (GI) bleeding. None of the patients had GI bleeding at the time. All patients received HeartWare CF-LVAD (HVAD, HeartWare Inc., Framingham, MA, USA). Six of the patients had relevant endoscopic findings and received therapy accordingly. None of these patients developed GI bleeding in the first 30 days after CF-LVAD implantation. Conclusion: Preoperative GI evaluation in patients undergoing elective CF-LVAD implantation might be beneficial in reducing GI bleeding postoperatively.